Osteoblast derived extracellular vesicles induced by dexamethasone: A novel biomimetic tool for enhancing osteogenesis in vitro - Zhang, Xing; Zhao, Qun; Zhou, Nan; Liu, Yu; Qin, Kang; Buhl, Eva Miriam; Wang, Xinhong; Hildebrand, Frank; Balmayor, Elizabeth R.; Greven, Johannes (Frontiers in Bioengineering and Biotechnology, 2023)
Extracellular vesicles (EVs) are newly appreciated communicators involved in intercellular crosstalk, and have emerged as a promising biomimetic tool for bone tissue regeneration, overcoming many of the limitations associated with cell-based therapies. However, the significance of osteoblast-derived EVs on osteogenesis has not been fully established. In this present study, we aim to investigate the therapeutic potential of EVs secreted from consecutive 14 days of dexamethasone-stimulated osteoblasts (OB-EVDex) to act as a biomimetic tool for regulating osteogenesis, and to elucidate the underlying mechanisms. OB-EVdex treated groups are compared to the clinically used osteo-inductor of BMP-2 as control. Our findings revealed that OB-EVDex have a typical bilayer membrane nanostructure of, with an average diameter of 178 ± 21 nm, and that fluorescently labeled OB-EVDex were engulfed by osteoblasts in a time-dependent manner. The proliferation, attachment, and viability capacities of OB-EVDex-treated osteoblasts were significantly improved when compared to untreated cells, with the highest proliferative rate observed in the OB-EVDex+BMP-2 group. Notably, combinations of OB-EVDex and BMP-2 markedly promoted osteogenic differentiation by positively upregulating osteogenesis-related gene expression levels of RUNX2, BGLAP, SPP1, SPARC, Col 1A1, and ALPL relative to BMP-2 or OB-EVDex treatment alone. Mineralization assays also showed greater pro-osteogenic potency after combined applications of OB-EVDex and BMP-2, as evidenced by a notable increase in mineralized nodules (calcium deposition) revealed by Alkaline Phosphatase (ALP), Alizarin Red (ARS), and von Kossa staining. Therefore, our findings shed light on the potential of OB-EVDex as a new therapeutic option for enhancing osteogenesis.